2010
DOI: 10.1007/s10346-010-0224-x
|View full text |Cite
|
Sign up to set email alerts
|

Meteorological effects on seasonal displacements of the Åknes rockslide, western Norway

Abstract: In the alpine topography along one of the long fjords with steep and high mountain sides in western Norway the large Åknes rockslide area is defined by a distinct back scarp rising from 800 to 1,000 m a.s.l. In 2004, an extensive monitoring program started, including establishment of a meteorological station above the upper tension crack, 900 m a.s.l. This paper evaluates the significance of meteorological conditions affecting the displacements recorded by five extensometers and two laser sensors in the tensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…These slopes can be kinematically predisposed to instabilities because of their pervasive jointing conditions and orientation, which controls both the strength and stiffness of the discontinuous medium, as well as the sizing of mobilised blocks. Based on these predisposing conditions, short-term transient phenomena, such as heavy rainfalls [ 5 ] or dynamic inputs (i.e., earthquakes or anthropic vibrations), can represent triggers able to lead the slope to failures, acting mutually on resistances and disturbing forces [ 6 , 7 , 8 , 9 , 10 ]. In addition to these common impulsive triggers [ 11 ], under specific climatic conditions where consistent thermal excursion exists, rock masses can also react to continuous cyclical thermal inputs, as the one due to solar radiation, which can operate on wider time-windows configuring as a preparatory factor for rock block failure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These slopes can be kinematically predisposed to instabilities because of their pervasive jointing conditions and orientation, which controls both the strength and stiffness of the discontinuous medium, as well as the sizing of mobilised blocks. Based on these predisposing conditions, short-term transient phenomena, such as heavy rainfalls [ 5 ] or dynamic inputs (i.e., earthquakes or anthropic vibrations), can represent triggers able to lead the slope to failures, acting mutually on resistances and disturbing forces [ 6 , 7 , 8 , 9 , 10 ]. In addition to these common impulsive triggers [ 11 ], under specific climatic conditions where consistent thermal excursion exists, rock masses can also react to continuous cyclical thermal inputs, as the one due to solar radiation, which can operate on wider time-windows configuring as a preparatory factor for rock block failure [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies revealed the complex nature of rockslides: many slides have multiple sliding surfaces; some are separated into zones with different displacement rates, while others are controlled by various factors (erosion, groundwater recharge, water level variation at a dam reservoir, etc.) (Aknes (Grøneng et al, 2010(Grøneng et al, , 2011, Ruinon (Crosta and Agliardi, 2003;Strozzi et al, 2005), Downie (Kalenchuk, 2010), and many others (El Bedoui et al, 2009;Froese et al, 2009;Barla et al, 2010;Helmstetter and Garambois, 2010;Zangerl et al, 2010;Gigli et al, 2011;Crosta et al, 2014)). Their complexity and the difficulty in assessing their behavior partly explain why rockslide mechanisms and processes are still poorly understood (Petley et al, 2005;Stead et al, 2006;Eberhardt, 2008;Glastonbury and Fell, 2008).…”
Section: Introductionmentioning
confidence: 93%
“…Temperature oscillations produce cyclic thermal strains in rock masses which result in deterioration processes associated with crumbling, cracking and jointing, opening/closing of joints/fractures, and in jointed rock masses may initiate thermally driven displacements ranging from slow creep (block ratcheting in terms of Pasten et al (2015), further toppling, and tilting to rapid movement in the form of rock cliffs overturning to rock falls. There are several slope failures, where no significant trigger was proposed and the rock failure mechanism remained unclear were recently recognized as hazards triggered by meteorological factors, including temperature variations (Dehn et al 2000;Vargas et al 2004;Krähenbühl et al 2004;Gunzburger et al 2011;Hales and Roering 2007;Vlcko et al 2009;Bakun-Mazor et al 2011Gischig et al 2011a, b;Grøneng et al 2011;Hatzor 2004). Treasury area (Petra, Jordan).…”
Section: Thermal Influencementioning
confidence: 99%